Oral Mucositis as a Side Effect of Myeloablative Chemotherapy in Hemato-oncological Patients - R. Pink; J. Pazdera; J. Vondráková; E. Faber; I. Skoumalová (Czech Dental Chamber, 2008)
The group of 20 patients treated for non-Hodgkin lymphomas and multiple myeloma was examined by stomatologists before planned autologous transplantation of stem cells. After tooth sanation and removal of the sources of local irritation and potential foci of odontogenic focal infection the patients were observed in the course of 4 to 5 weeks after transplantation for the occurrence of oral mucositis. Oral mucositis of 1st to 2nd degree (according to NCI-CTC classification) became manifest in the course of hemato-oncological treatment in all patients in relation to the type of chemotherapy. After successful termination of hemato-oncological treatment a spontaneous disappearance of oral mucositis developed. Low seriousness of oral complications of hemato-oncological therapy confirms the importance of careful stomatological preparation of the patient before planned autologous transplantation.